Sex Differences in Cardiovascular Disease Risk Factor Prevalence, Morbidity, and Mortality in Colombia: Findings from the Prospective Urban Rural Epidemiology (PURE) Study - Jose Patricio Lopez-Lopez; Martin Rebolledo-Del Toro; Daniel Martinez-Bello; Ángel A. Garcia-Peña; Gary O'Donovan; Maritza Perez-Mayorga; Johanna Otero; Sumathy Rangarajan; Salim Yusuf; Patricio Lopez-Jaramillo (Ubiquity Press, 2024)
Background: Controversies exist on whether the presence of cardiovascular risk factors and their association with major cardiovascular events (MACE) is different between men and women. Most of the evidence comes from high-income countries, hindering extrapolation of sociocultural and demographic factors of other regions. Objective: To evaluate sex differences in the prevalence of cardiovascular risk factors and the incidence of MACE and diabetes in Colombian adults. Methods: We performed a survival analysis from women and men aged 35-70 belonging to the Prospective Urban Rural Epidemiology-Colombia prospective study. Incidence rates for MACE composite (myocardial infarction, stroke, heart failure, death) and each outcome and diabetes were calculated. Kaplan-Meier curves and log-rank tests were performed. The association between demographic, behavioral, and metabolic variables with MACE and diabetes were evaluated with Cox proportional hazards models. Results: 7,552 participants (50±9.7 years) were included; 64% were women. Women had higher hypertension prevalence, body mass index, levels of total cholesterol, LDL-c, and HDL-c but lower triglycerides levels. Women were more sedentary but fewer smokers or active alcohol consumers and had higher educational levels. After 12-year mean follow-up (SD 2.3), the incidence rate of MACE composite was higher in men [4.2 (3.6-4.9) vs. 3.2 (2.8-3.7) cases per 1000 person-years]. Diabetes had the greatest association with MACE (HR = 2.63 95%CI:1.85;3.76), followed by hypertension (HR = 1.75 95%CI:1.30;2.35), low relative grip strength (HR = 1.53 95%CI:1.15;2.02), smoking (HR = 1.47 95%CI: 1.11;1.93), low physical activity (HR = 1.42 95%CI: 1.03;1.96). When evaluating risk factors by sex, only an increased waist-to-hip ratio was more strongly associated with MACE in men (p-interaction <0.05). Conclusions: The composite MACE outcome was higher in men despite having a lower overall burden of risk factors. The risk factors contribution was similar, leading us to reconsider the need to carrying out differentiated cardiovascular risk prevention and management campaigns, at least in our region.